Differentiating large absolute from relative expansions in De Novo Ventures — Are large capacity expansions sustainable in the long run? - FAN, Terence P. C. (Institutional Knowledge at Singapore Management University, 2017)
By considering how in many industries an augmentation in production capacity is necessary to bring about significant growth in sales or eventual profit, this study adds an important footnote to prevailing theories of firm survival and competitiveness in strategic management. First, it distinguishes between attempts for new ventures to grow their production from the outcome of their expansions. Second, this study delineates the role of large absolute versus relative growths in production and their differential implications on young, de novo ventures: the former being conducive to firm survival while the latter being detrimental to it. This prediction is supported empirically by 10 years of archival data from the intra-European passenger airline industry. In particular, many young firms would survive longer over the medium- to long-term if their relative growth is achieved at a lower but more sustainable rate.